(Legal) Language in Legaltech - Zorkóczy Miklós (PÁZMÁNY LAW REVIEW, 2023)
Legal terminology empowers words and expressions with specific meanings. Legal language used by lawyers is just like another language, with special wording, jargon and there are special legal instruments behind of the terminology. Using technology in the legal domain is not coding the law, tech engineers and lawyers should cooperate to let LegalTech tools work in full capacity with their effectiveness. In this way lawyers can be backed by technology, and in return for this their clients will receive enhanced customer experience. Lawyers can’t be substituted, but the legal tasks can be speeded up, and costs can be decreased. Large Language Models and Blockchain technology will be the next generation of LegalTech tools, just lawyers need to be careful until the tech achievements will be accurate and accountable enough for the quality legal work. This chapter gives a detailed presentation of how current LegalTech tools can support legal tasks, and what are the risks of next generation of technology.